Formulation of Solid Soap Preparation from Used Cooking Oils with Pineapple Peel Eco-enzyme - Salsabila, Luvena; Pradnya, Irene Nindita; Maulana, Ivan; Diana, Savira Rahma; Amalia, Annisa (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study explores the formulation and quality evaluation of solid soap made from recycled cooking oil enriched with fermented Ananas comosus (pineapple) peel extract. Three formulations were prepared using varying concentrations of pineapple peel eco-enzyme, while maintaining consistent proportions of palm sugar and water. The soap samples underwent physicochemical characterization in accordance with Indonesian National Standards (SNI). Results showed that all formulations had pH values within the acceptable range. Moisture content met regulatory limits in two formulations. All samples exhibited good foam stability, although the free fatty acid content exceeded permissible levels, likely due to extended hydrolysis during processing. Organoleptic assessment revealed uniform cream coloration, a characteristic aroma resembling soybean milk that decreased with higher eco-enzyme concentrations, and increased astringency corresponding to the concentration of pineapple extract. The soap maintained a solid texture with varying degrees of tackiness. This research demonstrates the potential for converting household waste into value-added products, while highlighting the need for further optimization to ensure compliance with commercial quality standards.